Epitaxial growth of β-Ga2O3 (−201) thin film on four-fold symmetry CeO2 (001) substrate for heterogeneous integrations. Issue 44 (7th October 2021) - Tang, Xiao; Li, Kuang-Hui; Liao, Che-Hao; Zheng, Dongxing; Liu, Chen; Lin, Rongyu; Xiao, Na; Krishna, Shibin; Tauboada, Jose; Li, Xiaohang
Abstract : High quality (−201) orientated β-Ga2 O3 thin films are obtained on four-fold symmetric cubic phase CeO2 (001) substrates and are fabricated into photodetectors with excellent photoelectrical performance. Abstract : β-Ga2 O3 is a wide bandgap semiconductor material that is promising for many fields such as gas sensors, UV detectors, and high-power electronics. Until now, most epitaxial β-Ga2 O3 thin films could only be realized on six-fold symmetric single crystal substrates including sapphire (0001), 3C-SiC (001), and native β-Ga2 O3 . In this report, we demonstrate the epitaxial growth of β-Ga2 O3 (−201) thin films on non-six-fold symmetric substrates, i.e., the CeO2 (001) substrate. Different from the conventional six-fold symmetric sapphire substrates, the four-fold symmetric cubic phase CeO2 (001) induces the formation of two sets of hexagonal-like atom frameworks with a mutual rotation angle of 90° in the β-Ga2 O3 (−201) plane. This is due to the small lattice mismatch between the β-Ga2 O3 (−201) plane and the CeO2 (001) plane in two directions: CeO2 [100]//β-Ga2 O3 [010] and CeO2 [010]//β-Ga2 O3 [010]. Besides, the valence band offset (VBO) and the conduction band offset (CBO) at the β-Ga2 O3 /CeO2 heterojunction are examined using high-resolution X-ray photoelectron spectroscopy (HR-XPS) and are estimated to be 1.63 eV and 0.18 eV, respectively, suggesting a type-II heterostructure. The obtained epitaxial β-Ga2 O3 thin films are fabricated into photodetectors (PDs), which show key photoelectrical characteristics that are similar to those of PDs using the conventional sapphire substrate. The results indicate the epitaxial β-Ga2 O3 thin films on CeO2 have a high crystallization quality, and thus are capable of producing various essential devices. Moreover, the epitaxy between β-Ga2 O3 (−201) and CeO2 (001) demonstrated in this work can pave the way for constructing heterostructures between β-Ga2 O3 and other cubic-phase functional materials, such as p-type semiconductors, piezoelectric semiconductors, and superconductors.